2017
DOI: 10.1080/16066359.2017.1311877
|View full text |Cite
|
Sign up to set email alerts
|

Young adults report increased pleasure from smoking cigarettes when drinking alcohol but not when using marijuana

Abstract: Background Among young adults, cigarette smoking is strongly associated with alcohol and marijuana use. The present study compared self-reported co-use of cigarettes and alcohol versus cigarettes and marijuana among young adults using cross-sectional survey data. Methods Participants were young adult cigarette smokers (age 18 to 25) who also reported past month alcohol or marijuana use enrolled in a randomized trial testing a smoking cessation intervention on Facebook. Participants self-reported extent of ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
1
12
0
3
Order By: Relevance
“…[20][21][22] Therefore, smokers represent a high-risk population that should also be appropriately screened and counseled regarding alcohol use. Furthermore, because drinking has been shown to represent a conduit for smoking [23][24][25][26] (ie, individuals tend to smoke more after consuming alcohol), reducing the incidence of drinking could also potentially lower smoking rates, particularly in instances of co-use.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] Therefore, smokers represent a high-risk population that should also be appropriately screened and counseled regarding alcohol use. Furthermore, because drinking has been shown to represent a conduit for smoking [23][24][25][26] (ie, individuals tend to smoke more after consuming alcohol), reducing the incidence of drinking could also potentially lower smoking rates, particularly in instances of co-use.…”
Section: Discussionmentioning
confidence: 99%
“…The association between e-cigarettes and alcohol, previously observed in other studies ( Morean et al, 2016 ; Schlienz & Lee, 2018 ; Taylor et al, 2017 ), together with data on social media trends ( Camenga et al, 2018 ; Chu et al, 2018 ; Sampasa-Kanyinga & Hamilton, 2018 ), indicates that use of the former is now a social activity ( Pepper et al, 2017 ; Yule & Tinson, 2017 ). This is particularly concerning not only in light of potential feedback effects due to the previously discussed outsize effects of peer behaviour, but also because e-cigarette use has been shown to increase the risk of cigarette smoking ( Barnett et al, 2015 ; Bold et al, 2018 ; Hammond et al, 2017 ), which also often co-occurs with alcohol use in social situations ( Berg et al, 2018 ; Gubner, Thrul, Kelly, & Ramo, 2018 ; Silveira et al, 2018 ), adding an additional layer of risk. Concerningly, early initiation of cigarette and alcohol co-use may increase the likelihood of opioid use ( Arterberry et al, 2016 ), and the possibility that vaping may come to replace smoking in this role cannot yet be discounted.…”
Section: Discussionmentioning
confidence: 99%
“…The Surgeon General’s Report concluded that women who smoke are more susceptible to depression and anxiety disorders than non-smokers, and that women trying to quit smoking relapse for different reasons than men [45]. Women are more likely to use smoking as a coping mechanism for stress, weight control and negative emotions, while men who smoke do so more for stimulation and in pleasurable settings [46]. Smoking is strongly associated with alcohol use among men [47], which is, at least partially, due to increased pleasure from smoking cigarettes when consuming alcohol [48].…”
Section: Discussionmentioning
confidence: 99%